Kepedulian Konsumen terhadap Label dan Informasi Bahan Tambahan Pangan (BTP) pada Label Kemasan Pangan di Kota Bogor - Hendry Noer Fadlillah; Lilis Nuraida; Eko Hari Purnomo (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Food additives are widely used in many food products. Producers must inform food additives used on the label of food products. Consumers are expected to read label to get information about the composition and ingredients of the product, including food additives. The aim of the research was to evaluate consumer awareness on food label and food additives in Bogor city. Data was collected by survey and processed statistically using SPSS. The respondents were divided into two groups. The first group was 15-24 years old, and the second group was >24 years old respondent. The numbers of respondent were 201 people for group 15-24 and 150 for >24 years old. The result showed, respondents who always read label were 33% of 15-24 group and 67% of >24 group. Of the respondent reading label, 95% of 15-24 years old and 73% of >24 years old recognized the term of food additives. Statistic analysis by Chi square showed correlation between education to the habit of respondents in reading label. Similar trend was also observed for income. Higher income and education respondents read label more frequent.